2017
DOI: 10.1002/2017gl074349
|View full text |Cite
|
Sign up to set email alerts
|

Modeling fracture propagation and seafloor gas release during seafloor warming‐induced hydrate dissociation

Abstract: The stability of marine methane hydrates and the potential release of methane gas to the ocean and atmosphere have received considerable attention in the past decade. Sophisticated hydraulic‐thermodynamic models are increasingly being applied to investigate the dynamics of bottom water warming, hydrate dissociation, and gas escape from the seafloor. However, these models often lack geomechanical coupling and neglect how overpressure development and fracture propagation affect the timing, rate, and magnitude of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 40 publications
2
31
0
Order By: Relevance
“…As shown in Stranne et al (2017), the upward transport of CH4 within destabilized hydrate-bearing 10 sediments can be divided into three flow regimes. These flow regimes depend on the sediment permeability, and encompass the expected range of permeabilities for hemipelagic sediments composed predominantly of terrigenous silts and clays (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…As shown in Stranne et al (2017), the upward transport of CH4 within destabilized hydrate-bearing 10 sediments can be divided into three flow regimes. These flow regimes depend on the sediment permeability, and encompass the expected range of permeabilities for hemipelagic sediments composed predominantly of terrigenous silts and clays (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Buffett & Archer (2004) speculate that slow diffusive transport of CH4 likely results in AOM within the sediments with negligible effect on climate, while a more rapid liberation of CH4 (in response to anthropogenic climate warming) can lead to fractured pathways within the sediment that bypass the microbial filter and allow for a larger proportion of the CH4 to reach the ocean and 20 atmosphere. This idea is supported by Stranne et al (2017), who showed that warming-induced hydrate dissociation in moderate to low permeability sediments (clays and silty-clays) leads to formation of hydraulic fractures and rapid release of CH4 from the seafloor.…”
Section: Introduction 25mentioning
confidence: 81%
See 3 more Smart Citations